Densification of Alumina and Silica in the Presence of a Liquid Phase - Singh V.K. (My University, 2025)
Alumina and silica powders were sintered at 1250° to 1460°C in the presence of liquid phases containing CaO, A12O3, and SiO2. The data were analyzed using the equation D = K log t +C and the Arrhenius equation. The activation energy for sintering decreases with increasing amounts of liquid phase. Copyright © 1981, Wiley Blackwell. All rights reserved